PARQUES TEMÁTICOS UNA OPCIÓN PARA EL TURISMO CULTURAL. ESTUDIO DE CASO: COMPLEJO ARQUEOLÓGICO DEL MONTE PUÑAY, CANTÓN CHUNCHI, PROVINCIA DE CHIMBORAZO, ECUADOR - Daniela Paulina Castillo Ortíz (European Scientific Journal, ESJ, 2015)
Ecuador is a diverse country for the variety of its natural ecosystems and multiculturalism, necessary conditions for developing tourism in a sustainable manner from the viewpoint of revitalization and heritage conservation. The cultural patrimony is reflected in the heritage of traditions and the archaeological legacy of the settlement of Andean civilizations throughout the territory. This is the case of Chunchi village, located at the south of Chimborazo province, where ancient attractions are in the process of deterioration due to environmental factors and tourist visitation. One of these attractions is the Archaeological Pyramid of Mount Puñay that in the Kichwa language means “Nativity Peak”. It was discovered in 2003 and it is one of the longest step pyramids on the planet, with the unique feature that no other pyramid in the world is built on the top of a mountain. The deterioration of heritage motivates its conservation; a valid strategy to strengthen heritage is to create a tourist destination that allows sustainable use in a theme park. This research shows that the Archaeological Site of Mount Puñay has untapped demand for tourist activities like hiking, participation in Andean ceremonies and museum tours, all part of the vision of sustainable tourism. In conclusion, the theme park fosters cultural tourism as an educational tool, heritage conservation, entertainment, real-life experiences, and development of good living for the people of the area.